(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Epidermolysis bullosa acquisita (EBA) is rare autoimmune blistering of the skin disease but not inherited and characterized by autoantibodies to collagen VII. It is a rare with an incidence rate of 0.26 / million population. Treatment include oral corticosteroids (E.g.: pre-dnisone), anti-inflammatory agents, and immunosuppressants (e.g.: azathioprine). Patients who are on long-term oral steroid treatment may be advised to take calcium and bisphosphonates to reduce the risk of osteoporosis that can be associated with steroid use. A case of 13 years old boy initially presented with bullous vesicular lesions all over the body. 5 months history of progressive trauma persuaded papules and vesicles on his hands, and face.